2023
DOI: 10.1111/jopr.13666
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the trueness and precision of conventional impressions versus digital scans for the all‐on‐four treatment in the maxillary arch: An in vitro study

Abstract: PurposeTo compare the accuracy of digitizing conventional impressions to intraoral surface scans for all‐on‐four treatment in the maxillary arch.Materials and methodsAn edentulous maxillary arch model with four implants placed in an all‐on‐four design was fabricated. Intraoral surface scans (n = 10) were obtained using an intraoral scanner after scan body insertion. For conventional polyvinylsiloxane impressions of the model, implant copings were inserted into the implant fixation for implant level, opened tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…These point clouds and meshes are aligned and fused, culminating in a 3D reconstruction of the scanned object (Marques et al., 2021; Zimmermann et al., 2015). Consistent with preceding studies, our research found no significant differences in the overall 3D deviation between the IOS and CI techniques (Marshaha et al., 2023; Papaspyridakos et al., 2016). Analysis of the individual analogs in the model revealed that at the analog of #10, the angular deviation of the CI group was smaller than the IOS group, with other analogs presenting no significant differences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These point clouds and meshes are aligned and fused, culminating in a 3D reconstruction of the scanned object (Marques et al., 2021; Zimmermann et al., 2015). Consistent with preceding studies, our research found no significant differences in the overall 3D deviation between the IOS and CI techniques (Marshaha et al., 2023; Papaspyridakos et al., 2016). Analysis of the individual analogs in the model revealed that at the analog of #10, the angular deviation of the CI group was smaller than the IOS group, with other analogs presenting no significant differences.…”
Section: Discussionsupporting
confidence: 92%
“…These point clouds and meshes are aligned and fused, culminating in a 3D reconstruction of the scanned object (Marques et al, 2021;Zimmermann et al, 2015). Consistent with preceding studies, our research found no significant differences in the overall 3D deviation between the IOS and CI techniques (Marshaha et al, 2023;Papaspyridakos et al, 2016). ages, and its precision depends on image orientation and camera calibration (Rivara et al, 2016).…”
Section: <001supporting
confidence: 88%
“…The use of digital intraoral scans for complete arch digital implant impressions has been widely researched and represents one of the most challenging clinical indications for achieving accuracy due to the lack of hard tissue references (Floriani et al., 2023; Gaikwad et al., 2022; Gómez‐Polo et al., 2022; Kaya & Bilmenoglu, 2022; Kernen et al., 2022; Lyu et al., 2022; Marshaha et al., 2023; Papaspyridakos et al., 2016; Sallorenzo & Gómez‐Polo, 2022). The majority of literature on the accuracy of complete‐arch digital intraoral implant impressions report favorable outcomes when assessment is performed under in‐vitro conditions.…”
Section: Discussionmentioning
confidence: 99%